TANGGUNG JAWAB SOSIAL, LINGKUNGAN DAN REPUTASI PERUSAHAAN: PENGUNGKAPAN PADA SITUS BANK - Juniati Gunawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
This research aims to provide evidence on the contents of corporate social and environmental responsibility (CSER) disclosures and company reputation on the three largest Banks (Bank Mandiri, Bank Central Asia and Bank Rakyat Indonesia) in Indonesia. CSER disclosures were measured through content analysis methods from the company’s’ websites, and company's reputation was measured through customer perceptions. The study was conducted through an online survey of 360 customers by undertaken non probability sampling and accidental sampling (convenience sampling). The results show that the majority of respondents agree with a good reputation after reading the Banks’ CSER websites. The dominant information of the Bank’s CSER website are community activities and programs, followed by environmental activities. Respondents stated that the Bank's reputation has been good and by reading the CSER website, the respondents felt more familiar with the Bank's activities. This familiarity adds a sense of customer’s closeness to the Bank. This research provides implementation contributions to the Bank and also provides empirical findings that can be used by other Banks in delivering CSER disclosures on the website. This research enhances to the depth of study in the field of CSER in the Indonesian context and contributes to the new insights for CSER research area.